The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/land11060782
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Carbon Visualizations in Landscape Design Based on Virtual Eye-Movement Behavior Preference

Abstract: Three-dimensional geovisualization in landscape design can be used to evaluate the efforts of mitigating CO2 emissions. This study evaluated subjects’ emotional preferences for 3D landscape design through an eye movement tracking experiment. In the case that the color of the building materials was positively correlated with low carbon emissions, green, blue, and gray were typical representatives of low carbon emissions. Through the eye movement tracking experiment, subjects’ emotional preferences for different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
(44 reference statements)
2
7
0
Order By: Relevance
“…Research result 3.1 confirmed that the higher the fixation frequency, the darker the color concentration of the heat map, which proves that the subjects are more interested in the roaming landscape. This is consistent with the research results of Liu et al (2021), Pei et al (2021) and Lin et al (2022) [ 41 , 42 , 43 ]. The variation trends of interest and thermodynamic diagram confirm that subjects have a strong interest in immersive experience, which is consistent with the research results of Lin et al (2022) and Wang et al (2016) [ 38 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Research result 3.1 confirmed that the higher the fixation frequency, the darker the color concentration of the heat map, which proves that the subjects are more interested in the roaming landscape. This is consistent with the research results of Liu et al (2021), Pei et al (2021) and Lin et al (2022) [ 41 , 42 , 43 ]. The variation trends of interest and thermodynamic diagram confirm that subjects have a strong interest in immersive experience, which is consistent with the research results of Lin et al (2022) and Wang et al (2016) [ 38 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with the research results of Liu et al (2021), Pei et al (2021) and Lin et al (2022) [ 41 , 42 , 43 ]. The variation trends of interest and thermodynamic diagram confirm that subjects have a strong interest in immersive experience, which is consistent with the research results of Lin et al (2022) and Wang et al (2016) [ 38 , 43 ]. Water landscape is not selected in the construction of the 3D roaming landscape.…”
Section: Discussionsupporting
confidence: 93%
“…Lipson-Smith et al (2020) and Díaz-Barrancas et al (2020) studied the visual elements of colour in space through virtual reality (VR) technology, carried out spatial construction and immersive colour presentation, invited subjects to conduct eye movement experiments, and completed the effectiveness and reliability of the evidence-based design process [ 14 , 15 ]. However, no related experiments in skin electrography were conducted, and the analysis of the explicit emotional processes of subjects was insufficient [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Green building is pivotal in mitigating the negative impacts of construction activities [147][148][149]. From the standpoint of reducing greenhouse gas emissions and energy use, green buildings have significant contributions due to their preference for recyclable materials and energy, low-carbon components, and sustainable operation and maintenance patterns [150][151][152][153]. Based on the survey by MacNaughton et al [154], the LEED-certified green buildings cumulatively eliminated 33,200 kilotons of CO 2 emissions, 91.12 kilotons of air pollutants, and 55.56 billion kW.h of electricity consumption from 2000 to 2016.…”
Section: The Importance Of Green Buildingsmentioning
confidence: 99%
“…Green buildings have significant contributions to the improvement of residents' comfort and health, users' experiences, and efficiency [151]. From the viewpoint of health and occupants' comfort, green buildings can effectively reduce the exposure of occupants to harmful materials and toxic gases [170,171].…”
Section: The Importance Of Green Buildingsmentioning
confidence: 99%